cách khác đơn giản hơn nhiều
Đk:\(x\ge1\)
\(pt\Leftrightarrow\sqrt{2\left(x-1\right)\left(x+4\right)}+\sqrt{2\left(x-1\right)\left(x+3\right)}-3\sqrt{x+4}-3\sqrt{x+3}-1=0\)
\(\Leftrightarrow\sqrt{2\left(x-1\right)\left(x+4\right)}-3\sqrt{x+4}+\sqrt{2\left(x-1\right)\left(x+3\right)}-3\sqrt{x+3}=1\)
\(\Leftrightarrow\sqrt{x+4}\left(\sqrt{2\left(x-1\right)}-3\right)+\sqrt{x+3}\left(\sqrt{2\left(x-1\right)}-3\right)=1\)
\(\Leftrightarrow\left(\sqrt{x+4}+\sqrt{x+3}\right)\left(\sqrt{2\left(x-1\right)}-3\right)=1\)
Xét Ư(1)={1;-1}={....}
Dễ nhé, tự làm nốt
Đk: \(x\ge1\)
\(pt\Leftrightarrow\sqrt{2x^2+6x-8}+\sqrt{2x^2+4x-6}-3\sqrt{x+4}-3\sqrt{x+3}-1=0\)
\(\Leftrightarrow\sqrt{2x^2+6x-8}-\frac{10}{3}\sqrt{x+3}+\frac{1}{3}\sqrt{x+3}-1\sqrt{2x^2+4x-6}-3\sqrt{x+4}=0\)
\(\Leftrightarrow\frac{2x^2+6x-8-\frac{100}{9}\left(x+3\right)}{\sqrt{2x^2+6x-8}+\frac{10}{3}\sqrt{x+3}}+\frac{x-6}{3\left(\sqrt{x+3}+3\right)}+\frac{2x^2+4x-6-9\left(x+4\right)}{\sqrt{2x^2+4x-6}+3\sqrt{x+4}}=0\)
Để đỡ rối ta đặt mấy cái mẫu \(\hept{\begin{cases}N=\sqrt{2x^2+6x-8}+\frac{10}{3}\sqrt{x+3}>0\\H=\sqrt{x+3}+3>0\\T=\sqrt{2x^2+4x-6}+3\sqrt{x+4}>0\end{cases}}\)
\(\Leftrightarrow\frac{18x^2-46x-372}{9N}+\frac{x-6}{3H}+\frac{2x^2-5x-42}{T}=0\)
\(\Leftrightarrow\left(x-6\right)\left(\frac{18x+62}{9N}+\frac{1}{3H}+\frac{2x+7}{T}\right)=0\)
Dễ thấy: \(\forall x\ge1\) thì \(\frac{18x+62}{9N}+\frac{1}{3H}+\frac{2x+7}{T}>0\)
\(\Rightarrow x-6=0\Rightarrow x=6\) (thỏa mãn)